2004
DOI: 10.5032/jae.2004.01086
|View full text |Cite
|
Sign up to set email alerts
|

A Tri-State Needs Assessment of Emotional Intelligence in Agricultural Education

Abstract: This study explored the importance and inclusion of emotional intelligence in the existing curriculum by agricultural education instructors. Although much research has been conducted about the importance of emotional intelligence in the realm of education, research in the area of emotional intelligence in agricultural education programs is limited. The concept of incorporating emotional intelligence into the agriscience curriculum is not a new idea. The very philosophy of agricultural education lends itself to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 4 publications
0
9
0
2
Order By: Relevance
“…"Children reared under conditions of little human contact can show huge improvements (30-50 IQ points) after being placed in normal environments" (ibid, p.4). Akers, Miller, Fraze, and Haygood (2004) believe emotional intelligence is a psychological construct not easily defined. However, Goleman (1995), cited in Akers et al (2004) defined emotional intelligence as simply "a different way of being smart" (p.84).…”
Section: General Scope and History Of Intelligencementioning
confidence: 99%
“…"Children reared under conditions of little human contact can show huge improvements (30-50 IQ points) after being placed in normal environments" (ibid, p.4). Akers, Miller, Fraze, and Haygood (2004) believe emotional intelligence is a psychological construct not easily defined. However, Goleman (1995), cited in Akers et al (2004) defined emotional intelligence as simply "a different way of being smart" (p.84).…”
Section: General Scope and History Of Intelligencementioning
confidence: 99%
“…Jensen (1998) went on to further explain that too often social and emotional education goes missing, leaving an opportunity to develop students in these areas. Leadership programs provide a natural fit to reinforce these skills (Akers, 2002). If we are challenged as a profession to prepare individuals for the working world and addressing the needs of employers, then it seems imperative that a strong emphasis be placed on emotional intelligence and critical thinking.…”
Section: Critical Thinking Dispositionmentioning
confidence: 99%
“…The core of experiential learning is to engage in self-evaluation, which, therefore, connects social emotional learning (SEL). Further, Akers, Miller, Fraze, and Haygood (2004) studied the importance and inclusion of emotional intelligence competencies in the existing agricultural education curriculum. Akers et al (2004) reported teachers believed emotional intelligence competencies were important and teachers believed they were incorporating the competencies in their curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Akers, Miller, Fraze, and Haygood (2004) studied the importance and inclusion of emotional intelligence competencies in the existing agricultural education curriculum. Akers et al (2004) reported teachers believed emotional intelligence competencies were important and teachers believed they were incorporating the competencies in their curriculum. However, empirical evidence was not readily apparent to assess whether agriculture teachers actually possessed the ability to teach SEL competencies.…”
Section: Introductionmentioning
confidence: 99%